PHARMACEUTICAL DEVELOPMENT & ANTI-MICROBIAL STUDY (IN VITRO) OF TANKANAMRUTA MALAHAR W.S.R. TO RASA TARANGINI - Patil, *Trupti Sadashiv; Deshmukh, Ashvini (International Journal of Ayurveda and Pharma Research, 2018)
â€œTankanâ€ which is among the Kshar traya mentioned in â€œKshar trik vidnyaniya trayodasha taranagaâ€ of Acharya Sadananda Sharma virachit Rasa tarangini. Tankan i.e., Borax (Na2B4O7 10H2O) is composed of boric acid & soda. It is a salt of tetra Boric acid, an important compound of Boron, which is also known as sodium biborate. Other Rasa Vaidyas also have included â€œTankanâ€ under the groups of Ksharatraya, Ksharapanchaka, Dravaka gana, Mitra panchaka etc. The present study was conducted to develop â€œTankanamruta malaharâ€ (pharmaceutically & to study its antimicrobial activity (In vitro). â€œTankanamruta malaharâ€ is a good combination of herbo-mineral preparation, which is indicated in Dushta vrana shodhan chikitsa or infected wounds. Though this formulation is from Ayurvedic classical text but there is a need to develop the standard procedure of preparation as they have faster & accurate results than oral administration of drug, so by the fusion of modern instruments & traditional methods of manufacturing procedures we have tried to make â€œTankanamruta malaharâ€ which contains Shuddha Tankan bhasma, Siktha taila, Sarji kshar, Shuddha pushpa kasis & Pipal twak kshar. Standardization describes all measures taken during manufacturing process like Shodhan, Maran, Kshar nirman & Siktha taila preparation etc & quality control leads to reproducible quality of particular product & in vitro study was performed to evaluate its anti-microbial activity against selected pathogens.